2007
DOI: 10.1128/iai.00119-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Commensal Bacterial Strains That Modulate Yersinia enterocolitica and Dextran Sodium Sulfate-Induced Inflammatory Responses: Implications for the Development of Probiotics

Abstract: An increasing body of evidence suggests that probiotic bacteria are effective in the treatment of enteric infections, although the molecular basis of this activity remains elusive. To identify putative probiotics, we tested commensal bacteria in terms of their toxicity, invasiveness, inhibition of Yersinia-induced inflammation in vitro and in vivo, and modulation of dextran sodium sulfate (DSS)-induced colitis in mice. The commensal bacteria Escherichia coli, Bifidobacterium adolescentis, Bacteroides vulgatus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…In fact, in the presence of costimulation with K. marxianus B0399 and LPS, significant decreases in the concentrations of the proinflammatory cytokines IFN-␥ and IL-12 and the chemokines IP-10 and IL-8 were demonstrated. In particular, a decreased level of production of IL-8 in response to inflammatory stimuli (LPS, TNF-␣, IL-1␤, and enteropathogenic bacteria) was described previously for a wide array of probiotic bacteria (7,17,25). Indeed, a massive and protracted release of IL-8 by colonocytes, associated with enteropathogenic infections, leads to persistent inflammation and epithelial barrier dysfunction (40).…”
Section: Discussionmentioning
confidence: 71%
“…In fact, in the presence of costimulation with K. marxianus B0399 and LPS, significant decreases in the concentrations of the proinflammatory cytokines IFN-␥ and IL-12 and the chemokines IP-10 and IL-8 were demonstrated. In particular, a decreased level of production of IL-8 in response to inflammatory stimuli (LPS, TNF-␣, IL-1␤, and enteropathogenic bacteria) was described previously for a wide array of probiotic bacteria (7,17,25). Indeed, a massive and protracted release of IL-8 by colonocytes, associated with enteropathogenic infections, leads to persistent inflammation and epithelial barrier dysfunction (40).…”
Section: Discussionmentioning
confidence: 71%
“…Induction of DSS colitis was performed according to a published protocol (31). Female C57BL/6 mice, 6-8 wk old with an initial weight of 17.6 6 3.2 g, were housed in groups of five/cage.…”
Section: Dss Colitis Modelmentioning
confidence: 99%
“…Various in vitro and animal studies with probiotics, including Escherichia coli strain Nissle 1917, have demonstrated the capacity of probiotics to reduce intestinal inflammation (29,42), to strengthen the intestinal barrier against pathogens (15,46), to increase the host innate immune functions (37), or to prevent adherent and invasive E. coli strains from adhering to and invading human intestinal epithelial cells (9). Indeed, limited clinical trials using E. coli strain Nissle 1917 or other microorganisms have suggested that this therapeutic strat-egy is efficacious in patients with chronic idiopathic inflammatory bowel diseases (IBD) (23,34,35,36), irritable bowel syndrome (32), and NEC (25).…”
mentioning
confidence: 99%